Effect of Time and Type of Infection of Xanthomonas axonopodis pv. cyamopsidis on Seedborne Infection in Clusterbean Cultivars - B.S. LAKRA (Seed Research, 2026)
Bacterial blight caused by Xanthomonas axonopodis pv. cyamopsidis is the most destructive disease of clusterbean in Haryana. The field and screen house experiments were conducted during 2001 and 2002 to see the effect of time and type of infection on disease development, per cent infection in seeds and seed yield/plant in three cultivars. The maximum (80%) seed infection was detected in Pusa Navbahar, followed by 21.2% in HG 365 and least 6.2% in HG 75 when plants were inoculated at 20 days after sowing under screen house conditions. High disease severity gave 51.5% infection in seeds of Pusa Navbahar, 11.6% in HG 365 and 3.5% in HG 375 under field conditions. No seed infection was observed in symptomless plants in any genotypes tested. The severe most category of infection caused reduction in seed yield/plant to the tune of 77.2% in Pusa Navbahar, 14.8% in HG 365 and 2.9% in HG 75. In clusterbean, high level of seeds are infected if plants receive infection prior to flowering.